The Dilemmas of Conducting Online Classes at Korean Language Training Courses in Indonesia during The Covid-19 Pandemic - Nugroho, Suray Agung (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
This paper recounts the implementation of our department’s community service to the teachers and owners of LPK Bahasa Korea (private institutions teaching Korean language to prospective migrant workers). Based on our preliminary survey prior to conducting the community service, we learned that a lot of LPK were facing dilemmas in implementing online classes. They found it difficult to adjust themselves into online classes during the Covid-19 pandemic. Although some knew that running the LPK would mean the livelihood of their household, they even had to stop operating simply due to their lack of knowledge in conducting online classes. At this point, they needed assistance in making the best use of online platforms and in preparing online contents of Korean language teaching. Based on this, we designed a two-day community service fully implemented online which attracted as many as 55 enthusiastic participants from various LPK across Indonesia. During the program, participants learned from our experiences and from others about the endless possibilities of using free online platforms so as to maintain their LPK’s livelihood and existence. Despite its limited time, participants managed to finally learn and choose the types of online platforms that suited their respective need. In particular, they also managed to learn practical ways in preparing Korean language-related online content to keep the enthusiasm and spirit of LPK students during and hopefully in the post-Covid19. ===== Paper ini mengulik ulang pelaksanaan program Pengabdian kepada Masyarakat (PkM) yang dilakukan oleh Prodi Bahasa dan Kebudayaan Korea kepada para pengajar dan pemilik LPK (Lembaga Pendidikan dan Ketrampilan) Bahasa Korea. Berdasarkan hasil survei awal sebelum PkM dilaksanakan, diketahui banyaknya LPK yang menghadapi dilema dalam menerapkan kelas daring. Mereka kesulitan menyesuaikan lembaganya dengan kelas-kelas daring selama pandemi Covid-19. Bahkan beberapa LPK berhenti beroperasi karena kurangnya pengetahuan terkait kelas daring, walaupun menjalankan LPK merupakan sumber penghasilan utama mereka. Pada titik itulah diketahui bahwa mereka memerlukan pendampingan untuk memanfaatkan platform pembelajaran daring yang tersedia serta untuk mempersiapkan konten-konten bahasa Korea secara daring. Berangkat dari keadaan inilah, Prodi Bahasa dan Kebudayaan Korea mendesain PkM 2 hari yang secara penuh diselenggarakan secara daring. PkM ini berhasil menarik minat 55 peserta dari berbagai LPK yang tersebar dari berbagai daerah di Indonesia Selama program berlangsung, para peserta belajar dari Prodi dan saling belajar dari peserta lain terkait berbagai macam platform online yang bisa mereka gunakan serta belajar juga cara membuat berbagai konten bahasa Korea secara praktis demi keberlangsungan keberadaan LPK mereka. Terlepas dari pendeknya waktu, para peserta berhasil belajar dan akhirnya memilih platform online yang cocok dengan LPK masing-masing. Yang lebih penting lagi, mereka tahu cara mempersiapkan konten bahasa Korea yang praktis untuk mempertahankan semangat belajar para peserta kursus di LPK baik selama masa pandemi maupun nanti di pasca-Covid19.